Antifungals and Drug Resistance - Chowdhury Mobaswar Hossain; Lisa Kathleen Ryan; Meeta Gera; Sabyasachi Choudhuri; Nazmun Lyle; Kazi Asraf Ali; Gill Diamond (Encyclopedia, 2022)
Antifungal drugs prevent topical or invasive fungal infections (mycoses) either by stopping growth of fungi (termed fungistatic) or by killing the fungal cells (termed fungicidal). Antibiotics also prevent bacterial infections through either bacteriostatic or bactericidal mechanisms. These microorganisms successfully develop resistance against conventional drugs that are designed to kill or stop them from multiplying. When a fungus no longer responds to antifungal drug treatments and continues to grow, this is known as antifungal drug resistance. Bacteria have an amazing capacity to become resistant to antibiotic action as well, and the effectiveness of the scarce antifungal arsenal is jeopardised by this antibiotic resistance, which poses a severe threat to public health.